Forced migration and household welfare in Indonesia - Irfan Raharjo; Marlina Ekawati; Wildan Syafitri (Faculty of Economics and Business, University of Muhammadiyah Malang, 2022)
Forced migration has a long-lasting impact on future generations. This study involves the application of logistic regression with marginal effect on data from the Indonesia Family Life Survey (IFLS) to find out the impact of forced migration on the welfare of parent and child households. The study findings show that forced migration can reduce the likelihood of a parent household becoming poor by 7.3%. For children who follow their parents migrating, the probability of becoming poor is also decreased by 9.82%. A decrease in household consumption of education and health, as well as the lack of asset ownership, can reduce human capital components. This finding shows the importance of supporting investment in human capital and physical capital for households experiencing forced migration to avoid intergenerational transmission of poverty.